Comorbidities and Assessment of Severity of Pediatric Acute Respiratory Distress Syndrome: Proceedings From the Pediatric Acute Lung Injury Consensus Conference. (June 2015) - Flori, Heidi; Dahmer, Mary K.; Sapru, Anil; Quasney, Michael W.
Abstract : Objectives: To determine the impact of patient-specific and disease-related characteristics on the severity of illness and on outcome in pediatric patients with acute respiratory distress syndrome with the intent of guiding current medical practice and identifying important areas for future research. Design: Electronic searches of PubMed, EMBASE, Web of Science, Cochrane, and Scopus were conducted. References were reviewed for relevance and features included in the following section. Settings: Not applicable. Subjects: PICU patients with evidence of acute lung injury, acute hypoxemic respiratory failure, and acute respiratory distress syndrome. Interventions: Not applicable. Measurements and Main Results: The comorbidities associated with outcome in pediatric acute respiratory distress syndrome can be divided into 1) patient-specific factors and 2) factors inherent to the disease process. The primary comorbidity associated with poor outcome is preexisting congenital or acquired immunodeficiency. Severity of disease is often described by factors identifiable at admission to the ICU. Many measures that are predictive are influenced by the underlying disease process itself, but may also be influenced by nutritional status, chronic comorbidities, or underlying genetic predisposition. Of the measures available at the bedside, both PaO2 /FIO2 ratio and oxygenation index are fairly consistent and robust predictors of disease severity and outcomes. Multiple organ system dysfunction is the single most important independent clinical risk factor for mortality in children at the onset of acute respiratory distress syndrome. Conclusions: The assessment of oxygenation and ventilation indices simultaneously with genetic and biomarker measurements holds the most promise for improved risk stratification for pediatric acute respiratory distress syndrome patients in the very near future. The next phases of pediatric acute respiratory distress syndrome pathophysiology and outcomes research will be enhanced if 1) age group differences are examined, 2) standardized datasets with adequately explicit definitions are used, 3) data are obtained at standardized times after pediatric acute respiratory distress syndrome onset, and 4) nonpulmonary organ failure scores are created and implemented.